Optimizing conditions for treatment and extraction of collagen from fan-bellied leatherjacket skin Monacanthus chinensis (Osbeck, 1765) - Thiet, Doan Thi; Ky, Pham Xuan; Vy, Phan Bao; Anh, Nguyen Phuong; Hy, Le Ho Khanh; Ha, Dao Viet; Boi, Vu Ngoc (Vietnam Journal of Marine Science and Technology, 2021)
The fan-bellied leatherjacket skin was treated to extract collagen by chemical method. The non-collagenous substances and the pigment in the skin were removed with NaOH and H2O2, respectively. Collagen was extracted with acetic acid. The treatment and extraction conditions were optimized by response surface methodology. The concentrations, skin/solution ratios (g/ml) and times were surveyed. The optimum conditions to remove the non-collagenous substances were as follows: the concentration of NaOH at 0.15M, the ratio (g/ml) at 1/13.9, time at 56.9 hours. Using H2O2 with the concentration at6%, the skin/solution ratio (g/ml) at 1/2, time at 10 minutes were suitable values for skin pigmentation removal. For collagen extraction, the concentration of acetic acid at 0.53M, skin/solution ratio at 1/9.6 g/ml and time in 59.6 hours were optimal.